TikTok Customer Engagement Behavior Based on User-Generated Content of Fashion Products in Indonesia - Natalia Mega Prasanti; Popy Rufaidah (Dinasti Publisher, 2024)
The study aims to assess the influence of user-generated content (UGC) of fashion products in Indonesia on TikTok customer engagement behavior. Quantitative method was employed in this study. Its involved 230 TikTok users that interacted with fashion content in Indonesia as respondent. Data analysis was conducted using a Structural Equation Modeling approach with Partial Least Square analysis. The result of the study reveals that UGC has a significant effect on customer engagement behavior. These results highlighted the important role of UGC as an important factor in that impacting the customer engagement on social media.